(untitled) (Medico Legal Update, 2020)
Knowledge on warning symptoms of high risk pregnancy as perceived by the antenatal mothers in a selected tertiary hospital, Kelambakkam, Kanchipuram District, Tamil Nadu, India’’. The objectives were to assess the knowledge on warning symptoms of high risk pregnancy perceived by the antenatal mothers to find out the association between the level of knowledge with demographic variables. The convenience sampling was used to select 60 Antenatal mothers . The data collection tools were validated and reliability was established. The data were collected by self-administered questionnaire. The collected data was Tabulated and Analyzed. Descriptive and Inferential statistical method were used. The study shows that 30% of the antenatal mothers had low level of knowledge, 57% of the antenatal mothers had moderate knowledge and 13% of the antenatal mothers had adequate knowledge regarding knowledge on warning symptoms of high risk pregnancy there was significant association between the knowledge and the selected demographic variables.